Death of a trophy wife - Levine, Laura, 1943- (Levine, Laura, 1943- Jaine Austen mystery., 2010)
When Marv Cooper's trophy wife Bunny is murdered during a lavish party, Jaine's friend Lance becomes the prime suspect. But Jaine knows he just couldn't have done it and sets out to find the real killer.